PENGUATAN PENGETAHUAN DAN PENDAMPINGAN PEROLEHAN IJIN CITES UNTUK EKSPOR TANAMAN DILINDUNGI BAGI MITRA PETANI MUDA JAWA TIMUR - Indah Camelia; Enny Narwati; Lina Hastuti (LPPM Institut Pendidikan Nusantara Global, 2025)
The fundamental problem faced by the partner farmers is the lack of knowledge and skills in fulfilling the trade documentation requirements for the protection of endangered plants and animals as regulated by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) of 1973. Due to limited understanding of export procedures and the requirements for protected plant products under CITES, the partners have resorted to exporting through the black market. As a result, the selling price of their products becomes lower, and the partners’ interests are less protected in case of shipping issues or payment problems. Moreover, sales through the black market can only be conducted on a small scale, which does not support the growth of the partner group’s business. The planned solution to address this problem is to enhance the partners’ knowledge and skills through outreach on CITES and intensive workshops on obtaining CITES permits. The program aims to improve their capability to independently acquire CITES permits, including preparing documents, registration, and fulfilling other technical requirements for future export of their products.